2018
DOI: 10.18805/ijar.b-3494
|View full text |Cite
|
Sign up to set email alerts
|

Hematological responses of common carp Cyprinus carpio administered with Neem (Azadirachta indica) leaf extraction

Abstract: The study investigated the effect of Neem Leaf Extract (NLE)—a herbal product on hematological parameters of common carp, Cyprinus carpio. Common carp fry were fed on diets having different levels of NLE [no NLE (D1), 0.25(D2), 0.5(D3), 1.0(D4), 1.5(D5), 2.0(D6) g/kg in basal diet containing rice bran and mustard] for 180 days in outdoor tanks. The results revealed an increase in TEC, TLC and PCV in groups D2-D6 compared to control (P less than 0.05), but increased PCV was observed only in D2, D3 and D4 groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
0
1
Order By: Relevance
“…The data presented in this report, showed that short term and long term treatment with IRACARP ® caused no significant change in the total white blood cell count. This finding is contrary to the result obtained from previous studies who reported that neem extract increased the total WBC following administration of substances that were toxic to animal hematology (Anokwuru et al, 2011;Kapinga et al, 2018;Kaur et al, 2019). However, Ashafa et al (2012) observed that neem extract significantly reduced WBC in wistar rats.…”
Section: Discussioncontrasting
confidence: 80%
“…The data presented in this report, showed that short term and long term treatment with IRACARP ® caused no significant change in the total white blood cell count. This finding is contrary to the result obtained from previous studies who reported that neem extract increased the total WBC following administration of substances that were toxic to animal hematology (Anokwuru et al, 2011;Kapinga et al, 2018;Kaur et al, 2019). However, Ashafa et al (2012) observed that neem extract significantly reduced WBC in wistar rats.…”
Section: Discussioncontrasting
confidence: 80%
“…These results suggest that supplementation could enhance the immune response involved in the control of infectious diseases, as observed in the pneumonia cases in our experiment. A similar phenomenon was observed in broiler chickens and carp fed Azadirachta indica extract, evidently increasing the number of W BC (Kwawukume et al, 2013;Kaur et al, 2019). A previous study showed that an extract of Phyllanthus niruri increased the functional maturation of dendritic cells (Nworu et al, 2010).…”
Section: Evaluation Of Health Statussupporting
confidence: 62%
“…The results showed that supplementation with the herbal mixture significantly increased hematocrit values (quadratic effect, P= 0.03), with a tendency to also increase hemoglobin levels (quadratic effect, P= 0.06), mean corpuscular volume (MCV; linear effect, P= 0.07) and mean corpuscular hemoglobin (MCH; linear effect, P= 0.1). Few studies have analyzed blood parameters in animals treated with extracts based on Phyllanthus niruri and Azadirachta indica, however Kaur et al (2019) showed similar results. In contrast, Nagalakshmi et al (1999), did not observe changes in the hemoglobin levels of broilers treated with Azadirachta indica extract; Gupta et al (2001) observed similar results with administration of Azadirachta indica extracts orally in rats for 60 days.…”
Section: Evaluation Of Health Statusmentioning
confidence: 93%